2004
DOI: 10.1111/j.1533-8525.2004.tb00012.x
|View full text |Cite
|
Sign up to set email alerts
|

News About Murder in an African American Newspaper: Effects of Relative Frequency and Race and Gender Typifications

Abstract: Previous scholarly research on selection bias in news about murder indicates that race and gender stereotypes and, to a much lesser extent, the relative frequency of particular murders explain why some homicides are made into news and others are not. However, previous research has directed nearly exclusive attention to white newspapers. The present rcsearch remedies this omission by directing attention to the factors that shape selection bias in news about murder in a big-city African American newspaper. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
2
8
0
2
Order By: Relevance
“…However, our analysis of Twitter-worthiness also reveals the disparity in papers’ Twitter mentions. Similar to earlier literature on news-worthiness, which has shown that the perceived news-worthiness raises questions about media biases [ 70 ], our analysis of Twitter-worthiness also shows that not every researcher or every publication benefits equally from Twitter. Our statistical analysis results show that publications on “social media research” topic, from G12 countries, in Q1 journals, and with OA status are more likely to be mentioned on Twitter, or in other words: are perceived to be more Twitter-worthy.…”
Section: Discussionsupporting
confidence: 82%
“…However, our analysis of Twitter-worthiness also reveals the disparity in papers’ Twitter mentions. Similar to earlier literature on news-worthiness, which has shown that the perceived news-worthiness raises questions about media biases [ 70 ], our analysis of Twitter-worthiness also shows that not every researcher or every publication benefits equally from Twitter. Our statistical analysis results show that publications on “social media research” topic, from G12 countries, in Q1 journals, and with OA status are more likely to be mentioned on Twitter, or in other words: are perceived to be more Twitter-worthy.…”
Section: Discussionsupporting
confidence: 82%
“…Lundman (2003) and Lundman et al (2004) noted that the Homicide Unit of the Columbus Police Department did not distinguish Hispanics from African American or White violators, and thus had to exclude Hispanics from the analysis (Lundman, 2003, p. 370).…”
Section: Notesmentioning
confidence: 97%
“…Missing from the homicide in the news media literature is how typification of other race or ethnic groups, such as Hispanics, serves as a criterion for assessing the newsworthiness of homicide incidents. Past homicide research has dealt with Hispanic victims and offenders by grouping them with Blacks into a "minority" race category or by excluding them from statistical analyses altogether (Lundman, 2003;Lundman, Douglass, & Hanson, 2004;Martinez & Lee, 1999). 2 Nonetheless, Hispanics are the fastest growing minority group in the United States (U.S. Bureau of the Census, 2007), and some U.S. cities, like Newark, have increasingly large Hispanic populations, making them the dominant population minority.…”
Section: The Present Studymentioning
confidence: 99%
“…Following the coding strategy employed by Montes et al (2020), an additional layer of coding was added to each reference denoting whether such arguments for and against prison education were made either explicitly or implicitly. This decision was informed by research suggesting a tendency within media coverage to avoid explicit, nuanced discussions of socio-political issues relating to race and class and/or poverty, often times because journalists are simply not conscious of the ways race and class might impact their work (Bowman 2018;Kim et al 2010;Lundman 2003). Doing so not only allows to capture the prevalence with which certain "frames" appear but also whether these frames are explicitly tied to cogent arguments, or merely offered as implicit indications of support or opposition.…”
Section: Analytic Strategymentioning
confidence: 99%